THE FARTHEST MOSQUE OR THE ALLEGED TEMPLE AN ANALYTIC STUDY - Wazeri, Yehia Hassan (Journal of Islamic Architecture, 2013)
AbstractThe Farthest Mosque (Al-Masjid Al-Aqsa in Jerusalem) has been associated in the consciousness of the Muslims, with The Sacred Mosque (Al-Masjid Al-Haram in Makkah) through a spiritual bond since the event of Isra’ (Night Journey) and Mi`raj (Ascension to Heaven). The objective of this study is to determine the orientation of the Farthest Mosque and illustrate the similarity in geometric shape (plan) and proportions, between the Farthest Mosque in Jerusalem and the sacred mosque (Al-Ka`bah) in Makkah, in the first part of the research. The second part of the research involves a study of some texts from the Old Testament that address the architectural and structural descriptions of the alleged temple, with the purpose of exposing whether glaring contradictions exist between the texts of the Old Testament themselves or between them and the real architectural and structural facts acknowledged by specialists in this field.Keywords: The Farthest mosque, the Alleged Temple, Al-Ka`bah, geometric similarity  AbstrakMasjid tertua (Masjid al-Aqsa di Jarusalem) telah dihubungkan dalam kesadaran umat muslim, dengan masjid suci (Masjidil Haram di Mekah) melalui ikatan spiritual sejak kejadian Isra’ (perjalanan malam) dan Mi’raj (kenaikan  ke  surga).  Tujuan  dari  kajian  ini  adalah  untuk  menentukan  orientasi  masjid  tertua  and menggambarkan kesamaan bentuk geometri (denah) dan proporsi, antara masjid tertua di Jarusalem dan masjid suci (Ka’bah) di Mekah, di bagian pertama penelitian. Bagian kedua penelitian melibatkan kajian beberapa tulisan dari surat wasiat kuno yang mengarah kepada deskripsi arsitektural dan struktural kuil, dengan tujuan mengekspos baik kontradiksi yang mencolok antara tulisan surat wasiat kuno itu sendiri maupun di antara mereka, dan fakta arsitektural dan struktural yang nyata diakui oleh spesialis di lapangan Kata kunci: masjid tertua, kuil, ka’bah, kesamaan geometri